Ultrasound-accelerated catheter-directed thrombolysis versus anticoagulation for the prevention of post-thrombotic syndrome (CAVA): a single-blind, multicentre, randomised trial. Issue 1 (January 2020) - Notten, Pascale; ten Cate-Hoek, Arina J; Arnoldussen, Carsten W K P; Strijkers, Rob H W; de Smet, André A E A; Tick, Lidwine W; van de Poel, Marlène H W; Wikkeling, Otmar R M; Vleming, Louis-Jean; Koster, Ad; Jie, Kon-Siong G; Jacobs, Esther M G; et al.
Summary: Background: Early thrombus removal might prevent post-thrombotic syndrome by preserving venous function and restoring flow. Previous trials comparing additional catheter-directed thrombolysis to standard treatment showed conflicting outcomes. We aimed to assess the benefit of additional ultrasound-accelerated catheter-directed thrombolysis for the prevention of post-thrombotic syndrome compared with standard therapy in patients with iliofemoral deep-vein thrombosis. Methods: We did a multicentre, randomised, single-blind, allocation-concealed, parallel group, superiority trial in 15 hospitals in the Netherlands. Patients aged 18–85 years with a first-time acute iliofemoral deep-vein thrombosis and symptoms for no more than 14 days were randomly assigned (1:1) to either standard treatment with additional ultrasound-accelerated catheter-directed thrombolysis or standard treatment alone. Randomisation was done with a web-based automatic programme and a random varying block size (2–12), stratified by age and centre. Standard treatment included anticoagulant therapy, compression therapy (knee-high elastic compression stockings; 30–40 mmHg), and early ambulation. Additional ultrasound-accelerated catheter-directed thrombolysis was done with urokinase with a starting bolus of 250 000 international units (IU) in 10 mL NaCl followed by a continuous dose of 100 000 IU/h for a maximum of 96 h through the Ekos Endowave-system. Adjunctive percutaneous transluminal angioplasty, thrombosuction, or stenting was performed at the discretion of the physician who performed the intervention. The primary outcome was the proportion of patients with post-thrombotic syndrome at 12 months diagnosed according to the original Villalta criteria—a Villalta-score of at least 5 on two consecutive occasions at least 3 months apart or the occurrence of venous ulceration—and was assessed in a modified intention-to-treat population of all randomly assigned patients who passed screening and started treatment. The safety analysis was assessed in the same modified intention-to-treat population. This study is complete and is registered at ClinicalTrials.gov, NCT00970619 . Findings: Between May 28, 2010, and Sept 18, 2017, 184 patients were randomly assigned to either additional ultrasound-accelerated catheter-directed thrombolysis (n=91) or standard treatment alone (n=93). Exclusion because of screening failure or early withdrawal of informed consent resulted in 77 patients in the intervention group and 75 in the standard treatment group starting allocated treatment. Median follow-up was 12·0 months (IQR 6·0–12·0). 12-month post-thrombotic syndrome occurred in 22 (29%) patients allocated to additional treatment versus 26 (35%) patients receiving standard treatment alone (odds ratio 0·75 [95% CI 0·38 to 1·50]; p=0·42). Major bleeding occurred in four (5%) patients in the intervention group, with associated neuropraxia or the peroneal nerve in one patient, and no events in the standard treatment group. No serious adverse events occurred. None of the four deaths (one [1%] in the intervention group vs three [4%] in the standard treatment group) were treatment related. Interpretation: This study showed that additional ultrasound-accelerated catheter-directed thrombolysis does not change the risk of post-thrombotic syndrome 1 year after acute iliofemoral deep-vein thrombosis compared with standard therapy alone. Although this trial is inconclusive, the outcome suggests the possibility of a moderate beneficial effect with additional ultrasound-accelerated catheter-directed thrombolysis. Further research is therefore warranted to better understand this outcome in the context of previous trials, preferably by combining the available evidence in an individual patient data meta-analysis. Funding: The Netherlands Organisation for Health Research and Development (ZonMw), Maastricht University Medical Centre, BTG-Interventional Medicine.